The impact of instruction on English as a foreign language high school students’ articulation of argumentative multimodal PowerPoint presentations - Martínez González, Rosa E.; Coyle, Yvette; Férez Mora, Pedro (Studies in Second Language Learning and Teaching, 2026)
This study examines the impact of multiliteracies pedagogy (MP) on the multimodal argumentative compositions of three focal 12- to 13-year-old students from intact mainstream English as a foreign language (EFL) classrooms in an ethnically diverse high school in Spain. Working from the premise that in content-focused education, learning-to-write and writing-to-learn are inseparable dimensions of second language (L2) learning and teaching, our study explores multimodal composing as a central site of L2 development. Before and after a four-week film-based instructional intervention, the students designed multimodal PowerPoint presentations on the sensitive issue of arranged marriage. Their pre- and posttest multimodal compositions were analyzed to identify structural, linguistic, and ideational improvements. The results revealed differing degrees of progress in the quality of students’ multimodal products, particularly in their incorporation of features of the argumentative genre, in their use of linguistic resources, and in their ability to combine semiotic resources to construct a more nuanced understanding of the topic. Pedagogical implications are suggested.